The Effect of Compensation, Discipline and Motivation on Employee Performance: The Case of PT Jaya Masawan Putera Sejahtera (JM Group) Palembang - Desmaliani, Marni; Rahayu, Sri; Trihandayani, Zaleha (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research, with practical implications, aims to determine the effect of compensation, work discipline, and work motivation on the performance of employees of PT Jaya Masawan Putera Sejahtera (JM Group) Palembang. The objects of this research are PT Jaya Masawan Putera Sejahtera (JM Group) Palembang employees. The sampling technique used the cluster sampling method with 315 employees. The research method used is associative research using primary data obtained from the results of questionnaire answers from 176 respondents. The analysis technique used is Multiple Linear Regression. This research shows that compensation, work discipline, and motivation not only significantly influence the performance of PT Jaya Masawan Putera Sejahtera (JM Group) employees but also have a positive influence. Partial testing shows a positive and significant influence of compensation, work discipline, and motivation on the performance of PT Jaya Masawan Putera Sejahtera (JM Group) Palembang employees, providing practical insights for effective human resource management.